Inventing our life [videorecording (DVD)] : the kibbutz experiment - Freilich, Toby Perl (First Run Features, 2012)
Set against the backdrop of its glorious 100-year history, Inventing Our Life: The Kibbutz Experiment reveals the heartbreak and hope of Israel's modern kibbutz movement as a new generation struggles to ensure its survival. Can a radically socialist institution survive a new capitalist reality? How will painful reforms affect those who still believe in the kibbutz experiment, and continue to call it home?